The Benefits Of The Storytelling Method On The Language Development Of 5-6 Year-Old Children At Lagan Pertiwi Paud - Rifkaamelia; Ali Akbarjono; Budrianto (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
Language development is one of the important aspects that must be optimally stimulated in early childhood education. One learning method that can support children's language development is the storytelling method. This study aimed to analyze the benefits of storytelling methods on the language development of children aged 5–6 years at PAUD Lagan Pertiwi, Lubuk Lagan Village, Seluma Regency. This research employed a descriptive qualitative approach. Data were collected through observation, semi-structured interviews, and documentation involving the principal, teachers, and children aged 5–6 years. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings revealed that storytelling methods using picture storybooks provided significant benefits in improving children's listening skills, enriching vocabulary, enhancing speaking skills, increasing the ability to express opinions, improving the ability to retell stories, and strengthening children's self-confidence in communication. The success of storytelling activities was supported by attractive picture storybooks, teachers’ storytelling skills, children's enthusiasm, school support, and a conducive learning environment. However, several obstacles were identified, including differences in children's language abilities, limited concentration spans, low self-confidence among some children, limited storybook variations, and classroom management challenges. Therefore, storytelling methods can be recommended as an effective learning strategy to optimize language development in early childhood.